Archaeology of Buddhism :recent discoveries in South Asia - Sanjay Garg, Ed (SAARC, 2017)
The archaeology of Buddhism involves the recovery and scientific investigation of the material remains of past cultures that can illuminate the periods, events and other descriptions mentioned in the religious texts. The geographical distribution of the adherents of Buddhism spread rapidly after the mahaparinirvana of the Lord Buddha – ‘The enlightened one’. India was the fulcrum of Buddhism in the ancient world, but today, the whole of South Asia – covering Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan and Sri Lanka – is replete with innumerable material remains of the past which can be associated with the Lord Buddha and Buddhism. Many of these sites have been inscribed on the UNESCO list of world heritage properties. This book contains 40 contributions by 55 leading archaeologists, historians and other experts in the field of South Asian art and archaeology. These contributions range from the country reports on recent discoveries of Buddhist sites and remains in South Asia, to in-depth studies in Buddhist archaeology, art and architecture of this region. Other topics included in this volume discuss the cultural Geography of the Buddhist archaeological sites, their digital mapping using advanced ICT tools, The archaeology of the Buddhist monasteries as well as their relationship with contemporary society. These essays read together present a narrative that transcends borders and defies time. It is hoped that this volume will underscore the imperative need for institutionalizing the archaeology of Buddhism as a specialized branch of the study of our shared heritage and will promote a better appreciation of the archaeological heritage of Buddhism that binds the SARC nations with a common historical and cultural thread.